THE EFFECT OF RICE SHARECROPPING ON FARMERS’ AND LANDOWNERS’ WELFARE IN PITU RIAWA AND DUA PITUE SIDENRENG RAPPANG - Nurhikma Tasri; Ruslang T; Rudi Arafah (Cateris Paribus Journal, 2026)
The agricultural sector, particularly the food crops subsector, is the backbone of Indonesia’s rural economy. However, most farmers do not own their own land and therefore rely on the tenant farming system as a means of livelihood. This study aims to analyze the impact of the rice sharecropping system on the welfare of tenant farmers and landowners in Pitu Riawa and Dua Pitue subdistricts, Sidenreng Rappang Regency. This phenomenon is important to study because the dominant practice of verbal profit-sharing agreements is prone to creating legal uncertainty and economic injustice, as mandated for protection under Law No. 2 of 1960 on Profit-Sharing Agreements. The study employs a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews with 10 tenant farmers and 10 landowners, and field documentation. The results indicate that the tenant farming system makes a significant contribution to tenant farmers’ household income, enabling them to meet daily needs, cover education costs, and save. For landowners, this system provides passive income while maintaining land productivity. Profit-sharing agreements are made verbally with proportions varying between 50:50 and 60:40. The success of the system is influenced by external factors such as weather, pests, and water availability. This study recommends formalizing agreements in writing, as well as government support in the form of fertilizer subsidies, irrigation improvements, and the provision of agricultural tools.